Pengaruh Rasio Likuiditas dan Rasio Solvabilitas terhadap Kinerja Keuangan: Studi Kasus pada Perusahaan Transportasi dan Logistik yang Terdaftar di BEI Periode 2020–2023 - Aiman Luqmanul Akbar; Dedy Syahyuni (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
The purpose of this study is to determine how the financial performance (Y) of transportation and logistics companies listed on the Indonesia Stock Exchange during the 2020-2023 period correlates with liquidity (X1) and solvency (X2) ratios. This research utilizes multiple linear analysis methods with secondary data and SPSS tools. The population consists of 37 companies, with 10 companies as research samples. The analysis results show that the liquidity ratio (X1) does not significantly affect the financial performance (Y) of transportation and logistics companies listed on the Indonesia Stock Exchange; the t-test probability value for this ratio is 0.078, greater than 0.05. In the same way, the t-test for the solvency ratio found a probability value of 0.259, which is also greater than 0.05, indicating that the solvency ratio also does not affect financial performance (Y). On the other hand, the f test value is 0.141, which is also greater than 0.05. Overall, the financial performance (Y) of transportation and logistics companies listed on the Indonesia Stock Exchange is not significantly affected by the liquidity ratio (X1) and solvency ratio (X2) variables. From these results, it can be concluded that only ten percent of financial performance is influenced by solvency and liquidity ratios. Other factors not considered in this study affect the other ninety percent.